Identifikasi Bakteri Tanah di Kebun Botani Biologi FKIP Universitas Jambi - Okti Chairani; Retni S Budiarti; Winda Dwi Kartika (BIO-SITE |Biologi dan Sains Terapan, 2016)
Soil bacteria has important role in the life cycle of an ecosystem. Their life activities affect the characteristics of the biologic, physical, and chemical environment. Biology study program of education faculty in Jambi University has a plot of land made into a botanical garden. Thus, this botanical garden needs some information about the fertility of the land used, and one of them is to know the type of bacteria in its soil as a biological factor. The purpose of this research is to determine the genus of bacteria found in soil of Biology Botanical Garden at Education Faculty (FKIP) of Jambi University, Mendalo. This research was conducted from April to July of 2015, in both biology botanical garden and biology laboratory at Education Faculty of Jambi University. The kind of this research is explorative descriptive. Soil sample was collected by using 4 squared plots measuring 12 m x 12 m. In each plot made 5 subplots and soil samples was taken from 3 points of each subplot by random sampling. The identification was done by observing colony morphology, gram staining, and biochemical tests. The result of this research was gained gained 9 genus of bacteria, they were Paracoccus, Nitrosococcus, Bacillus, Cellulomonas, Acinetobacter, Micrococcus, Pseudomonas, Azotobacter, and Zymomonas. It is suggested to further researchers to study about other microorganisms in the soil Biology Botanical Garden that have role in maintaining and improving soil fertility there.